You're my heart, you're my soul - Bohlen, Dieter; Oksala, T. T.; SONY BMG Music Entertainment (Finland); Leningrad Cowboys (yhtye) (SONY BMG Music Entertainment (Finland), 2006)
1 kappale.
Keywords: Leningrad Cowboys : singlet